The Principles Governing Transactions Involving the Right of Restitution and Conditional Sale in Islamic Jurisprudence, Iranian Law, and Egyptian Law - Farzad Baradaran Kenari; Soosan Narimani; Alireza Salami (پژوهشنامه حقوق تطبیقی)
Conditional sales and the right of restitution in contracts are concepts that have distinct, yet occasionally overlapping, effects in transactions. In Iran's registration law, these concepts are often used interchangeably. This is evident in jurisprudential texts and legal regulations. In Iranian law, the acceptance of conditional sales has gained traction; however, it is inaccurate to equate the concepts of transactions, the right of restitution, and conditional sales. In Egyptian law, the prevailing opinion among most Egyptian jurists is that since the customer does not acquire ownership, they should reject the transaction. Consequently, the seller retains the right to claim restitution without being bound by the statutory period for such claims. The purpose of this article is to examine the principles governing transactions involving the right of restitution and conditional sales within the legal frameworks of Iran and Egypt. This analysis employs a descriptive-analytical method. We conclude that the principles governing transactions with the right of restitution and conditional sales differ significantly between the two legal systems. In Iranian jurisprudence and law, the foundation of such transactions is based on the right of restitution, as articulated in Emami's jurisprudence. Conversely, in Egyptian jurisprudence and law, these transactions are rooted in Hanafi jurisprudence, which is primarily derived from verses, hadiths, traditions, and reason. These elements are crystallized within the core of legal provisions.